TEACHERS' ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IMPROVES THE QUALITY OF SCHOOL ORGANIZATIONS - Ekawati Praharti; Corry Yohana; Suparno Suparno (Green Publisher, 2023)
This study aims to find factors that can increase the Organizational Citizenship Behavior (OCB) of DKI Jakarta teachers through research on the influence of transformational leadership, school culture and organizational commitment to OCB. This research method is descriptive correlation using a quantitative approach. The population in this study were vocational teachers based on data from the DKI Jakarta Education Office totaling 1846 people. The sampling technique used proportional random sampling with ? = 5% and the number of samples based on the Slovin formula was 328 people. The determination of the schools to be used as research locations was carried out by means of a lottery totaling 15 schools from 5 regions in DKI Jakarta. The data analysis technique used begins with descriptive analysis, to describe the characteristics of each research variable. Then using Structural Equation Modeling with Amos Software version 22. The findings of this study are: 1) There is a direct effect of transformational leadership (X1) on organizational commitment (X3) of 0.450. 2) There is a direct influence of school culture (X2) on organizational commitment (X3) of 0.279. 3) There is a direct effect of transformational leadership (X1) on Organizational Citizenship Behavior (OCB) (Y) of 0.485. 4) There is a direct influence of school culture (X2) on Organizational Citizenship Behavior (OCB) (Y) of 0.371. 5) There is a direct effect of organizational commitment (X3) on Organizational Citizenship Behavior (OCB) (Y) of 0.470. 6) There is a direct effect of transformational leadership (X1) on school culture (X2) of 0.130. 7) There is an indirect effect of transformational leadership on Organizational Citizenship Behavior (OCB) (Y) mediated by organizational commitment (X3) of 0.212. 8) There is an indirect effect of school culture (X2) on Organizational Citizenship Behavior (OCB) (Y) mediated by organizational commitment of 131